How the Spouse's Retirement Affects the Cognitive Health of Individuals in China: A Fresh Evidence From the Perspective of Social Interaction - Xiong, Xiaohan; Li, Rui; Yang, Hualei (Frontiers in Public Health, 2021)
Background: With the rapid aging of global population, the health consequences of retirement reform are debated greatly. However, most previous studies are limited to the effects on individual themselves, and pay scant attention to the perspective of social interaction. Driven by the practical and academic motives, this study investigates the impacts of the spouse’s retirement on individual cognitive health among Chinese dual-earner couples. Methods: We first build a simultaneous-equations model. Then, using the data from the 2010 to 2018 China Family Panel Studies (CFPS), we choose the fixed-effects model and adopt the fuzzy regression discontinuity design method to analyze. Besides, we check the validity and robustness of the results. Finally, we employ the mediating effect model to explore the mechanisms. Results and Conclusions: The spouse’s retirement has significantly negative direct and indirect effect on individual cognitive health. Husbands’ retirement has a stronger adverse spillover effect than wives’ retirement, and wives’ cognitive health is more vulnerable to the social interaction effect. The direct spillover effect of husbands’ retirement is -0.503 and that of wives’ retirement is -0.312, the indirect spillover effect of husbands’ retirement is -0.36 and that of wives’ retirement is -0.279. In addition to the social interaction effect of cognition between the couples, we also find that the decrease in household income is an important mechanism, and that the increased exercise frequency can somewhat mitigate the adverse spillover effect.